Environmental audit in dairy farms: A method to identify and prevent impacts on groundwater - Cisneros Basualdo, Nicolás Eloy (2025)
Dairy farming is a key economic activity in Argentina. To achieve sustained growth, farmers adopted various strategies, leading to intensified milk production, but also to increased and accelerated environmental impacts. This study sought to analyze the environmental performance of water use and management in dairy farms in the 'Mar y Sierras' region of the province of Buenos Aires. A diagnostic environmental audit was implemented in five diverse case studies, which were chosen based on production size, location, and socio-productive dynamics. The study involved three stages: (1) a holistic environmental characterization of the farms, (2) farm visits, interviews and chemical analysis of groundwater and wastewater, and (3) proposing mitigation measures for each farm. Production stages vary across farms depending on their physical environment. The critical points identified included the interrelationship between groundwater management, wastewater treatment and disposal. Mitigation proposals tailored to the specific environment of each farm were suggested. Additionally, goals and objectives were established to ensure compliance with current environmental regulations. In conclusion, the environmental audit method enabled to determine the dynamics and operations of the farms, identify the most environmentally critical points based on each farm's natural and socio-economic context and assess their compliance with current environmental regulations.